A novel cost-effective heterostructured Fe-based medium-entropy alloy with high cryogenic strength and ductility - Hongyan Wang; Qiuyu Gao; Zhimin Yang; Chongxun Fang; Yongfu Cai; Juqiang Zhang; Xin Zhao; Ran Wei (Journal of Materials Research and Technology)
There is a strong demand for metallic materials with exceptional comprehensive properties in various engineering applications. In this work, a novel cost-effective Fe62Ni15Cr13Si7Al3 (at%) medium entropy alloy (MEA) was designed. Through the utilization of cold-rolling and short-duration annealing techniques, we successfully achieved a partially recrystallized microstructure in the MEA, primarily consisting of nearly single face-centered cubic (FCC) microstructure with NiAl-rich B2 nano-precipitates. The MEA demonstrates exceptional high tensile yield strengths (>1 GPa) at both room and cryogenic temperatures. Furthermore, it exhibits an impressive ultimate tensile strength of ∼1.8 GPa and high uniform ductility of ∼45% at 77 K. Particularly, the MEA exhibits the ultra-high specific yield strength (200 MPa cm3/g) at 77 K, compared to previously reported medium/high entropy alloys (M/HEAs). Through microstructure analysis and molecular dynamic simulation, it has been determined that the outstanding cryogenic strength-ductility synergy can be attributed to multiple deformation mechanisms, including Lüders deformation, deformation nanotwins, stacking faults, B2 nano-precipitates, Lomer-Cottrell locks, back stress strengthening, and deformation-induced martensitic transformation. These findings offer an exciting opportunity for designing cost-effective M/HEAs with superior properties surpassing those of conventional alloys.